2018
DOI: 10.3390/atmos9090365
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Atmospheric Transport and Rain–Vapor Exchange to Near-Surface Water Vapor in the Zhanjiang Mangrove Reserve, Southern China: An Isotopic Perspective

Abstract: Coastal mangroves are increasingly recognized as valuable natural resources and important sites of water and carbon exchange. In this study, we examine atmospheric water cycling in the boundary layer above a coastal mangrove forest in southern China. We collected site observations of isotopic ratios in water vapor and precipitation along with core meteorological variables during July 2017. Our evaluation of these data highlights the influences of large-scale atmospheric transport and rain–vapor exchange in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Lai et al (2018) examined the atmospheric water cycling above a coastal mangrove forest in Southern China. They also found that the substantial increase of atmospheric water vapour d‐excess is related to the passage of a tropical typhoon, “Talas” (Lai et al, 2018). This variation in air mass and monsoon activity also caused inter‐annual differences in isotopes between 2019 and 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lai et al (2018) examined the atmospheric water cycling above a coastal mangrove forest in Southern China. They also found that the substantial increase of atmospheric water vapour d‐excess is related to the passage of a tropical typhoon, “Talas” (Lai et al, 2018). This variation in air mass and monsoon activity also caused inter‐annual differences in isotopes between 2019 and 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis of this application is that the d‐excess of water vapour is closely linked to the environmental conditions during the kinetic fractionation processes (Araguas‐Araguas et al, 2000; Craig, 1961). Hence, the strong sensitivity of d‐excess to local atmosphere relative humidity (RH) can place better constraints on the water transport processes than the analyses of water vapour δ 2 H and δ 18 O alone (Lai et al, 2018; Wei & Lee, 2019). Previous work has traced both the ocean moisture sources (Dahinden et al, 2021; Gonzalez et al, 2016; Salamalikis et al, 2015) and continental moisture recycling (Aemisegger et al, 2014; Fiorella et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingraham and Criss (1993) have noted that the water vapour isotopic composition and the exchange rate can change due to different geographical areas and weather conditions. Furthermore, precipitation–water vapour exchange takes different forms for different types of rainfall events (Lai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most values that fall along the linear regression line reflect the equilibrium isotopic exchange, whereas the points that deviate may reflect secondary evaporation (Figure 10). This deviation indicates that equilibration between boundary layer vapour and rainfall was incomplete and further suggests that non‐equilibrium isotopic fractionation may have occurred through partial evaporation of the raindrops (Lai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%